KOMUNIKASI DALAM PERSEPSI MASYARAKAT TENTANG KEBIJAKAN PEMERINTAH DIMASA PANDEMI : Studi Kasus Pada Kebijakan Vaksin Covid-19 - Chontina Siahaan; Donal Adrian (Kinesik, 2021)
The government's strategy in preventing the spread of COVID-19 is to implement policies regarding the injection of the corona 19 vaccine to the entire community. This study aims to analyze and describe the communication process in public perceptions of the COVID-19 vaccine policy by the Palu City government. The research method used qualitative. Data collection techniques, namely observation and in-depth interview. The results showed that the government policy regarding the COVID-19 vaccine is a stimulus that can generate perceptions from the public as a target. Based on the perception that the people in Palu City, Central Sulawesi, responded well to the policy of injecting the COVID-19 vaccine for a healthy and prosperous Indonesia.